AN ANALYSIS REGARDING THE EFFECTS OF THE EMPLOYEES AND WORKING PROCESS UPON THE LEVEL OF CUSTOMER SATISFACTION AT PT TELKOM TBK BOGOR - Syarief Gerald Prasetya; Yustiana Wardhani (STIE Binaniaga, 2017)
Customer’s satisfaction and dissatisfaction is not new phenomena of Business in Indonesia. From the customer’s perspective has mostly complained about the goods or services with low quality, expensive price, inappropriate guarantee, etc. On the other side (in this case producer) there’s a response to fix it. A lot of facts may cause the customer satisfied, for example, reasonable price, interesting promotion, professional labour, work procedure and creative product with high standard. By finding and developing customer’s satisfaction factors, a company will perform a rapid development. Therefore this thesis has identified the employees’ factor and working process affecting the customer’s satisfaction in order to focus the research.Main problem of this research is whether the employees or the working process has been affecting the customer’s satisfaction rate either simultaneously or partially? According to this problem so the purpose is to notice the employees and the working process that have affected the customer’s satisfaction rate simultaneously or partially. This research also has applied the theories which explain about the factors that are affecting the customer’s satisfaction including the definitions. From that point of view a hipothesis is defined that the employees and the working process are affecting the customer’s satisfaction rate. either simultaneously or partially. The analysis report shows that the employees and the process of work/work procedur have been really the result of the customer satisfaction rate simultaneously. This can be proved with the test by using F-test method and the result shows that the correlation between the employees and the working procedure has really affected the customer’s satisfaction rate which is it has been accepted. Then the test of the effect of the customer’s satisfaction rate which is the result of the correlation between the employees and the working procedure using t-test method, and the result shows that the employees and the working procedure partially has have really affected the customer’s satisfaction rate, and it is accepted. As the conclusion, we could say that the correlation between the employees and the process of work/working procedure has a really been affecting the customers satisfaction rate, either simultaneously or partialy. The writer can only suggest the company (PT. Telkom Tbk Bogor) to pay more attention to the front liners employees to become permanent employees because I think it could be such a motivation for them to give a much better services to the customers, by providing a continuously training to the front liners, especially, always maintaining the consistency of high quality of the services as well as solid environment among departments, so it would give a guarantee to the customers, regarding the due date of a complaint or or the new lines services to complete.Keywords: customer satisfaction, work process